DC-SIGN and CD150 have distinct roles in transmission of measles virus from dendritic cells to T-lymphocytes. - Lot de Witte; Rory D de Vries; Michiel van der Vlist; Selma Yüksel; Manja Litjens; Rik L de Swart; Teunis B H Geijtenbeek (PLoS Pathogens, 2008)
Measles virus (MV) is among the most infectious viruses that affect humans and is transmitted via the respiratory route. In macaques, MV primarily infects lymphocytes and dendritic cells (DCs). Little is known about the initial target cell for MV infection. Since DCs bridge the peripheral mucosal tissues with lymphoid tissues, we hypothesize that DCs are the initial target cells that capture MV in the respiratory tract and transport the virus to the lymphoid tissues where MV is transmitted to lymphocytes. Recently, we have demonstrated that the C-type lectin DC-SIGN interacts with MV and enhances infection of DCs in cis. Using immunofluorescence microscopy, we demonstrate that DC-SIGN+ DCs are abundantly present just below the epithelia of the respiratory tract. DC-SIGN+ DCs efficiently present MV-derived antigens to CD4+ T-lymphocytes after antigen uptake via either CD150 or DC-SIGN in vitro. However, DC-SIGN+ DCs also mediate transmission of MV to CD4+ and CD8+ T-lymphocytes. We distinguished two different transmission routes that were either dependent or independent on direct DC infection. DC-SIGN and CD150 are both involved in direct DC infection and subsequent transmission of de novo synthesized virus. However, DC-SIGN, but not CD150, mediates trans-infection of MV to T-lymphocytes independent of DC infection. Together these data suggest a prominent role for DCs during the initiation, dissemination, and clearance of MV infection.